Efektivitas Layanan Bimbingan Kelompok dalam Meningkatkan Kecerdasan Emosional Siswa - Muliani, Vebri; Sano, Afrizal (MASALIQ, 2024)
Low emotional intelligence can have negative impacts on yourself and others because you cannot take an appropriate attitude. Therefore, group guidance is very necessary to increase students’ emotional intelligence. The research method used is Quantitative with a Pre-experiment design Experimental method. The reseach subjects 11 students MTsN 11 Agam those selected using Purposive Sampling technique. Data analysis used the Wilcoxon Signed Rank Test. The results of student data analysis after following group guidance 5 times stated that there was a significant difference in scores between the pretest and posttest of students’emotional intelligence after following group guidance.